Analisis Sentimen Media Sosial Kementerian RI: Respons Warganet Memanfaatkan TextBlob Analyser - Gumilang, Mukhamad Angga; Abdillah, Fauzan; Amin, Muhammad Yusril; Hasan, M (Jurnal Sosioteknologi, 2024)
Nowadays, People can express their opinions, criticism, suggestions, and even blasphemy thanks to social media. Through sentiment analysis, this study attempts to investigate how online users react to social media accounts of the Ministry of the Republic of Indonesia by using the Purposive Sampling method. From 2022 to 2023, we collected 100 comments from users on Instagram, Facebook, and Twitter. The election was made by looking at the posts that received the most likes and comments. After that, TextBlob techniques were used to analyze the emotions of 3400 comments collected from 34 ministries. Based on Presidential Regulation Number 68 of 2019, our analysis is focused on four groups of ministries: coordinators and three group ministries. The Ministry of Group II had the highest percentage of unfavorable sentiment, reaching 15.8%. On the other hand, Group III ministries lead with the largest percentage of favorable opinions at 54.6%. This data provides an idea of how responsive the administration has been for the past two years to the public's wishes revealed on social media.